Examining Masculinity in Short Stories “Buaian Rahim Patriarki” By Ni Wayan Wijayanti - Yostiani Noor Asmi Harini; Aisya Mardiani; Iis; Novianti Fitria Rahmadhona; Intan Satia Hotimah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
The literary work in the form of a short story entitled